Biological patch as well as preparation method and application thereof
By setting non-crosslinked parts and crosslinked parts in the matrix of the biological patch and controlling their poor porosity, the problem of excessive degradation rate of biological patches in vivo is solved, and the degradation rate is matched with the tissue repair process is achieved, and the comprehensive repair of damaged tissue is promoted.
Patent Information
- Application Number
- CN202411802393.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-18
AI Technical Summary
The degradation rate of existing biological patches is too fast in vivo, and the degradation rate does not match the tissue repair process, resulting in failure of repair or prolonging healing time.
A biological patch is designed, and its matrix includes a non-crosslinked portion and a crosslinked portion. The porosity of the non-crosslinked portion is greater than the porosity of the crosslinked portion, and the porosity difference is greater than or equal to 5%, to regulate the overall degradation rate of the biological patch.
Extend the degradation time of biological patches in the body, maintain good mechanical properties, and maintain high collagen biological activity, so that its degradation rate matches the tissue repair process, thereby better promoting the comprehensive repair of damaged tissue.
Smart Images

Figure CN119633168A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical materials, in particular to a biological patch and a preparation method and application thereof. Background Art
[0002] Existing biological patches degrade too quickly after being implanted in the body. Generally, a cross-linking process is used to improve the degradation performance of the biological patch. However, there is still a problem that the degradation rate of the biological patch does not match the tissue repair process, and there is even excessive cross-linking, which leads to reduced collagen bioactivity in the biological patch, prolonged healing time, and even repair failure. Summary of the invention
[0003] Based on this, it is necessary to provide a biological patch and its preparation method and application to address the above problems. The biological patch can prolong its degradation time in the body, maintain good mechanical properties, maintain high collagen bioactivity, and the degradation rate in the body matches the tissue repair process, which can better promote the comprehensive repair of damaged tissues.
[0004] A biological patch comprises a matrix, wherein along the thickness direction of the biological patch, the matrix comprises a non-crosslinked part and a crosslinked part, wherein the thickness ratio of the non-crosslinked part to the crosslinked part is 1:99-99:1, the porosity of the non-crosslinked part is greater than the porosity of the crosslinked part, and the porosity difference is greater than or equal to 5%.
[0005] In one embodiment, the average porosity of the non-cross-linked portion is 40%-90%;
[0006] And / or, the average porosity of the cross-linked portion is 0.1%-40%.
[0007] In one embodiment, the porosity of the cross-linked portion is the same from the cross-linked portion to the non-cross-linked portion, or the porosity of the cross-linked portion increases gradually.
[0008] In one embodiment, when the porosity of the cross-linked portion is the same, the thickness ratio of the non-cross-linked portion to the cross-linked portion is 1:9-9:1.
[0009] In one embodiment, when the porosity of the cross-linked portion increases gradually, the thickness ratio of the non-cross-linked portion to the cross-linked portion is 1:99-99:1.
[0010] In one embodiment, when the porosity increases gradually, the cross-linked portion contains a polysaccharide polymer, and the average cross-linking degree of the polysaccharide polymer is 0.1%-50%.
[0011] In one embodiment, the polysaccharide polymer is selected from at least one of chitosan, chitosan derivatives, cellulose, cellulose derivatives, guar gum, tamarind gum, sodium carboxymethyl cellulose, and sodium carboxymethyl starch.
[0012] In one embodiment, the non-cross-linked portion includes a first non-cross-linked portion and a second non-cross-linked portion, and the cross-linked portion is arranged between the first non-cross-linked portion and the second non-cross-linked portion. From the first non-cross-linked portion to the second non-cross-linked portion, the pores of the cross-linked portion first decrease and then increase.
[0013] In one embodiment, the thickness ratio of the first non-cross-linked portion to the second non-cross-linked portion is 1:9-9:1.
[0014] In one embodiment, a bonding layer is further provided between the non-crosslinked portion and the crosslinked portion, and the thickness of the bonding layer is 0.1%-20% of the total thickness of the substrate;
[0015] And / or, the material of the matrix is selected from dermal acellular matrix or collagen.
[0016] In one embodiment, the thickness of the biological patch is 0.5 mm-5.5 mm;
[0017] And / or, the average pore size of the biological patch is 0.1 μm-500 μm, and the average porosity is 10%-80%.
[0018] A method for preparing a biological patch comprises the following steps:
[0019] Mixing a polysaccharide polymer compound aqueous solution and a cross-linking agent to obtain a mixed solution;
[0020] Placing the mixed solution on any surface of a base material, allowing the mixed solution to gradually penetrate into the base material to a preset depth to perform a gradient cross-linking reaction to form a cross-linked part and a non-cross-linked part, and obtaining a biological patch after washing and freeze-drying, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 1:99-99:1, the porosity of the non-cross-linked part is greater than the porosity of the cross-linked part, and the porosity difference is greater than or equal to 5%;
[0021] Alternatively, a polysaccharide polymer compound aqueous solution and a cross-linking agent are mixed to obtain a mixed solution;
[0022] Placing the mixed solution on any surface of the base material, allowing the mixed solution to gradually penetrate into the base material to a preset depth to perform a gradient cross-linking reaction to form a cross-linked portion and a non-cross-linked portion A, and obtaining a prefabricated biological patch after washing;
[0023] An adhesive is placed on the surface of the non-crosslinked part A of the prefabricated biological patch, and then a new matrix material is bonded to the prefabricated biological patch so that the non-crosslinked part A and the new matrix material together constitute a non-crosslinked part. After water bathing and freeze drying, a biological patch is obtained, wherein the thickness ratio of the non-crosslinked part to the crosslinked part is 1:10-10:1, the porosity of the non-crosslinked part is greater than the porosity of the crosslinked part, and the porosity difference is greater than or equal to 5%.
[0024] In one embodiment, the method for preparing the biological patch further satisfies at least one of the following conditions:
[0025] (1) The mass fraction of the polysaccharide polymer compound in the polysaccharide polymer compound aqueous solution is 3%-10%, wherein the polysaccharide polymer compound aqueous solution is at least one selected from a chitosan aqueous solution, a chitosan derivative aqueous solution, a cellulose aqueous solution, a cellulose derivative aqueous solution, a guar gum aqueous solution, a tamarind gum aqueous solution, a sodium carboxymethyl cellulose aqueous solution, and a sodium carboxymethyl starch aqueous solution;
[0026] (2) The viscosity of the mixed solution is 0.01 Pa·s-40000 Pa·s, and the pH value is 8-14;
[0027] (3) The mass fraction of the cross-linking agent in the mixed solution is 0.1%-5%, wherein the cross-linking agent is selected from at least one of an aldehyde cross-linking agent, a carboimide, and a glycidyl ether;
[0028] (4) The mass fraction of the polysaccharide polymer compound in the mixed solution is 0.1%-5%;
[0029] (5) The gradient cross-linking reaction temperature is 25°C-50°C, and the gradient cross-linking reaction time is 0.5h-48h;
[0030] (6) The cleaning treatment step includes: first washing with water, then replacing with alcohol, then soaking in an aqueous solution of an anionic descaling agent with a mass fraction of 0.2% to 1% to swell for 1 h to 2 h, and finally placing in water;
[0031] (7) The matrix material is selected from dermal acellular matrix or collagen.
[0032] A method for preparing a biological patch comprises the following steps:
[0033] The polysaccharide polymer compound aqueous solution and the cross-linking agent are mixed, and then an alkaline solution is added to adjust the alkalinity to obtain a mixed solution;
[0034] The mixed solution is placed on any surface of the first matrix material and the second matrix material respectively, and the mixed solution is gradually infiltrated into the first matrix material and the second matrix material to a preset depth to perform a gradient cross-linking reaction to form a first gradient cross-linked portion, a first non-cross-linked portion, a second gradient cross-linked portion, and a second non-cross-linked portion, and then washed and freeze-dried to obtain a first intermediate and a second intermediate;
[0035] A binder is placed on the surface of the first gradient cross-linked part of the first intermediate and / or the second gradient cross-linked part of the second intermediate, and then the first intermediate and the second intermediate are bonded together, so that the first gradient cross-linked part and the second gradient cross-linked part together constitute a cross-linked part, the first non-cross-linked part and the second non-cross-linked part together constitute a non-cross-linked part, and the cross-linked part is located between the first non-cross-linked part and the second non-cross-linked part, and a biological patch is obtained after water bathing and freeze drying, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 1:99-99:1, the porosity of the non-cross-linked part is greater than the porosity of the cross-linked part, and the porosity difference is greater than or equal to 5%.
[0036] In one embodiment, the method for preparing the biological patch further satisfies at least one of the following conditions:
[0037] (1) The mass fraction of the polysaccharide polymer compound in the polysaccharide polymer compound aqueous solution is 3%-10%, wherein the polysaccharide polymer compound aqueous solution is at least one selected from a chitosan aqueous solution, a chitosan derivative aqueous solution, a cellulose aqueous solution, a cellulose derivative aqueous solution, a guar gum aqueous solution, a tamarind gum aqueous solution, a sodium carboxymethyl cellulose aqueous solution, and a sodium carboxymethyl starch aqueous solution;
[0038] (2) The viscosity of the mixed solution is 0.01 Pa·s-40000 Pa·s, and the pH value is 8-14;
[0039] (3) The mass fraction of the cross-linking agent in the mixed solution is 0.1%-5%, wherein the cross-linking agent is selected from at least one of an aldehyde cross-linking agent, a carboimide, and a glycidyl ether;
[0040] (4) The mass fraction of the polysaccharide polymer compound in the mixed solution is 0.1%-5%;
[0041] (5) The gradient cross-linking reaction temperature is 25°C-50°C, and the gradient cross-linking reaction time is 0.5h-48h;
[0042] (6) The cleaning treatment step includes: first washing with water, then replacing with alcohol, then soaking in an aqueous solution of an anionic descaling agent with a mass fraction of 0.2% to 1% to swell for 1 h to 2 h, and finally placing in water;
[0043] (7) The first matrix material and the second matrix material are independently selected from dermal acellular matrix or collagen.
[0044] An application of the biological patch as described above in repairing tissue damage.
[0045] The biological patch of the present invention, by setting a non-crosslinked part and a crosslinked part, limiting the thickness of the non-crosslinked part and the crosslinked part and the relationship between the porosity of the two, utilizes the difference between the degradation time of the non-crosslinked part and the crosslinked part and the collagen bioactivity, can effectively regulate the overall degradation rate of the biological patch in the body, and control it within a suitable range, balance the relationship between the collagen bioactivity and the degradation time in the biological patch, so that the biological patch can prolong its degradation time in the body, maintain good mechanical properties while maintaining high collagen bioactivity, and the degradation rate in the body matches the tissue repair process, thereby better promoting the comprehensive repair of injured tissue. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 This is a schematic structural diagram of a biological patch according to a first embodiment of the present invention;
[0048] Figure 2 This is a schematic structural diagram of a biological patch according to a second embodiment of the present invention;
[0049] Figure 3 is a schematic structural diagram of a biological patch according to a third embodiment of the present invention;
[0050] Figure 4 for Figure 3 Schematic diagram of the structure of the cross-linked part;
[0051] Figure 5 This is an electron microscope image of the longitudinal cross-section of the biological patch prepared in Example 1 of the present invention.
[0052] Reference numerals:
[0053] 1. Non-cross-linked portion; 2. Cross-linked portion; 3. First non-cross-linked portion; 4. Second non-cross-linked portion. DETAILED DESCRIPTION
[0054] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0056] like Figure 1-4 As shown, the biological patch provided by the present invention includes a non-crosslinked part 1 and a crosslinked part 2 along the thickness direction of the biological patch, i.e., the direction indicated by the arrow, wherein the non-crosslinked part 1 is used to directly contact with the tissue to be repaired. It can be understood that when the biological patch is implanted into the body for repairing damaged tissues, since the non-crosslinked part 1 has the high biological activity and faster degradation performance of collagen, it directly contacts with the damaged tissue after implantation, and can quickly release the cytokines required in the early stage of the tissue repair process, inducing the rapid growth of the tissue in the early stage after implantation, while the collagen biological activity of the crosslinked layer is relatively low, and the degradation time is longer, which can prolong the overall degradation time of the biological patch in the body, and is conducive to comprehensive repair of the damaged tissue.
[0057] Among them, the thickness ratio of the non-cross-linked part 1 and the cross-linked part 2 is 1:99-99:1, preferably, the thickness ratio is 1:50-50:1, the porosity of the non-cross-linked part 1 is greater than the porosity of the cross-linked part 2, and the porosity difference is greater than or equal to 5%, preferably, the porosity difference is greater than or equal to 10%, and further preferably, the porosity difference is greater than or equal to 20%.
[0058] In the present invention, by limiting the thickness of the non-cross-linked part 1 and the cross-linked part 2 and the relationship between the porosity thereof, the difference in degradation time and collagen bioactivity between the non-cross-linked part 1 and the cross-linked part 2 can be effectively utilized to regulate the overall degradation rate of the biological patch in the body and control it within an appropriate range, thereby balancing the relationship between the collagen bioactivity and degradation time in the biological patch, so that the biological patch can extend its degradation time in the body, maintain good mechanical properties while maintaining high collagen bioactivity, and the degradation rate in the body matches the tissue repair process, thereby better promoting the comprehensive repair of injured tissue.
[0059] Optionally, the average porosity of the non-cross-linked portion 1 is 40%-90%. Specifically, the average porosity of the non-cross-linked portion 1 includes but is not limited to 40%, 50%, 60%, 70%, 80%, and 90%.
[0060] Furthermore, the average porosity of the cross-linked part 2 is 0.1%-40%, and specifically, the average porosity of the cross-linked part 2 includes but is not limited to 1%, 5%, 10%, 20%, 30%, and 40%. In this way, the average porosity of the non-cross-linked part 1 and the average porosity of the cross-linked part 2 can be adjusted, so that the biological patch can better have both high collagen bioactivity and mechanical properties.
[0061] It is understandable that, in the present invention, the porosity of the cross-linked portion 2 will affect the degradation rate of the biological patch during tissue repair and the level of collagen bioactivity. In the present invention, the porosity of the cross-linked portion 2 in the direction from the cross-linked portion 2 to the non-cross-linked portion 1 can be the following two situations:
[0062] The first case: the porosity of the cross-linked part 2 is the same from the cross-linked part 2 to the non-cross-linked part 1, such as Figure 1 As shown. Further, the thickness ratio of the non-crosslinked part 1 to the crosslinked part 2 is 1:9-9:1. Such a setting is conducive to better regulating the degradation time of the entire biological patch and the biological activity of collagen, and better promoting its degradation speed in the body to match the tissue repair process.
[0063] The second case: the porosity of the cross-linked part 2 increases gradually from the cross-linked part 2 to the non-cross-linked part 1, such as Figure 2As shown, with such a configuration, the gradient cross-linking of the cross-linked part 2 in the thickness direction can be achieved by regulating the change in the porosity of the cross-linked part 2, so that the greater the distance from the non-cross-linked part 1, the longer the degradation time, thereby guiding the gradient degradation of the biological patch in the thickness direction, and this gradient degradation can better match the tissue ingrowth process, thereby better providing good mechanical support throughout the entire process of tissue regeneration, while being able to appropriately degrade to provide space for tissue ingrowth, thereby better achieving comprehensive repair of injured tissue.
[0064] Therefore, the second case is preferred in the present invention.
[0065] Optionally, when the porosity of the cross-linked part 2 increases gradually, the thickness ratio of the non-cross-linked part 1 to the cross-linked part 2 is 1:99-99:1, preferably, the thickness ratio is 1:10-10:1, and more preferably, the thickness ratio is 1:4-4:1. Such a configuration is conducive to further prolonging the degradation time of the biological patch in the body, improving the mechanical properties, better maintaining the high biological activity of collagen, and thus better repairing the injured tissue.
[0066] Optionally, when the porosity increases gradually, the cross-linked portion 2 contains a polysaccharide polymer, and the average cross-linking degree of the polysaccharide polymer is 0.1%-50%. This arrangement is conducive to further regulating the porosity of the cross-linked portion.
[0067] Furthermore, the polysaccharide polymer is selected from biodegradable polysaccharide polymers, and the biodegradable polysaccharide polymer is selected from at least one of chitosan, chitosan derivatives, cellulose, cellulose derivatives, guar gum, tamarind gum, sodium carboxymethyl cellulose, and sodium carboxymethyl starch. In this way, the degradation time of the biological patch in the body can be prolonged, and while providing continuous mechanical properties, it has good biocompatibility with the human body and improves the biological safety of the biological patch.
[0068] Figure 3-Figure 4 The structure of the biological patch of the third embodiment of the present invention is combined with Figure 3As shown, the non-crosslinked part 1 includes a first non-crosslinked part 3 and a second non-crosslinked part 4, and the crosslinked part 2 is arranged between the first non-crosslinked part 3 and the second non-crosslinked part 4. From the first non-crosslinked part 3 to the second non-crosslinked part 4, the pores of the crosslinked part 2 first decrease and then increase. In this way, both sides of the biological patch are non-crosslinked parts 1 with high collagen biological activity and faster degradation performance. When implanted into the body, both sides of the biological patch are directly in contact with the damaged tissue, which can induce the tissue to grow rapidly from both sides in the early stage after implantation; while the degradation time of the middle crosslinked layer is longer, and the greater the distance from the first non-crosslinked layer and the second non-crosslinked layer, the longer the degradation time. Therefore, the tissue can be further guided to grow into the middle of the biological patch in the thickness direction, and finally achieve tissue healing on both sides.
[0069] In the present invention, the thickness ratio of the first non-crosslinked part 3 to the second non-crosslinked part 4 is 1:99-99:1. Specifically, the thickness ratio of the first non-crosslinked part 3 to the second non-crosslinked part 4 includes but is not limited to 1:50, 1:9, 1:5, 1:1, 5:1, 9:1, 50:1, preferably 1:50-50:1, more preferably 1:9-9:1, and more preferably 1:5-5:1. Such a configuration is conducive to better promoting the rapid healing and regeneration of tissues on both sides of the body.
[0070] It is understandable that the thickness of the first non-crosslinked portion 3 and the second non-crosslinked portion 4 in the present invention can be the same or different, preferably the same. Such a configuration is conducive to improving the consistency of uniform growth of tissues on both sides.
[0071] In one embodiment, the non-crosslinked portion 1 and the crosslinked portion 2 are integrally formed. This configuration simplifies the structure.
[0072] Optionally, a bonding layer is further provided between the non-crosslinked part 1 and the crosslinked part 2 . Such a configuration is beneficial to improving the bonding force between the non-crosslinked part 1 and the crosslinked part 2 .
[0073] The thickness of the bonding layer is 0.1%-20% of the total thickness of the substrate. Specifically, the thickness of the bonding layer includes but is not limited to 0.1%, 0.5%, 1%, 5%, 10%, 15%, and 20%.
[0074] Optionally, the material of the matrix is selected from dermal acellular matrix or collagen, preferably dermal acellular matrix.
[0075] Optionally, the thickness of the biological patch is 0.5mm-5.5mm; specifically, the thickness of the biological patch includes but is not limited to 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm, 5.5mm. This arrangement can effectively ensure the mechanical properties of the biological patch while improving its fit with the damaged tissue.
[0076] Optionally, the average pore size of the biological patch is 0.1μm-500μm, preferably 5μm-200μm; specifically, the average pore size of the biological patch includes but is not limited to 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 100μm, 120μm, 150μm, and 200μm.
[0077] Furthermore, the average porosity of the biological patch is 10%-80%; specifically, the average porosity of the biological patch includes but is not limited to 10%, 20%, 30%, 40%, 50%, 60%, 70%, and 80%.
[0078] In the present invention, by setting appropriate thickness, pore size, and average porosity, the biological patch can not only better simulate the normal tissue structure, provide cell matrix components such as scaffolds for cell growth, better carry cell groups that are beneficial to tissue repair and regeneration, and promote tissue repair and regeneration; it also has good suture strength, tensile strength, and tear resistance, and can provide the mechanical reinforcement required for tissues in the regeneration and repair process. Specifically, the suture strength of the biological patch is 8N-80N, the maximum tensile force is 10N-180N, and the tear strength is 5N-50N.
[0079] At the same time, the present invention also provides Figure 1 The preparation method of the biological patch of the structure shown specifically comprises the following steps:
[0080] S11, placing the matrix material in a crosslinking agent aqueous solution, and performing a crosslinking reaction at a temperature of 25°C-35°C for 10h-15h to obtain a crosslinked matrix material, wherein the mass fraction of the crosslinking agent in the crosslinking agent aqueous solution is 0.1%-2%; it can be understood that in this process, the crosslinking agent reacts with the collagen molecules in the matrix material to form a crosslinked part 2.
[0081] In one embodiment, the matrix material is selected from dermal acellular matrix or collagen.
[0082] Furthermore, the crosslinking agent is selected from at least one of an aldehyde crosslinking agent, carboimide, genipin, glycidyl ether or an epoxy crosslinking agent, preferably an aldehyde crosslinking agent, carboimide or glycidyl ether, and more preferably glutaraldehyde, carboimide or 1,4-butanediol glycidyl ether.
[0083] It should be noted that different types of cross-linking agents require different environments for cross-linking with collagen active substances in the matrix material. Therefore, the acidity and alkalinity of the cross-linking agent aqueous solution can be adjusted according to the type of cross-linking agent. For example, when the cross-linking agent is selected from aldehyde cross-linking agents or glycidyl ethers, an alkaline solution can be added to the cross-linking agent aqueous solution to adjust the pH value to 12-13; when the cross-linking agent is selected from carbonimide, the cross-linking agent aqueous solution can be controlled to be weakly acidic.
[0084] S12, washing the cross-linked matrix material with water until it is neutral, and freeze-drying it to obtain a freeze-dried matrix material.
[0085] S13, placing a binder on the surface of a new base material, and then placing a freeze-dried base material on the surface of the base material containing the binder, forming a cross-linked portion 2 and a non-cross-linked portion 1 through freeze-drying, and obtaining Figure 1 In the biological patch shown, the thickness ratio of the non-crosslinked part 1 to the crosslinked part 2 is 1:9-9:1, the porosity of the non-crosslinked part is greater than the porosity of the crosslinked part, and the porosity difference is greater than or equal to 10%. It can be understood that the crosslinked matrix material serves as the crosslinked part 2, and the crosslinking of the crosslinked part 2 is uniformly distributed, that is, the porosity is the same, and the new matrix material serves as the non-crosslinked part 1.
[0086] Furthermore, the adhesive is selected from fibrin glue or collagen solution. Such a configuration can not only improve the bonding force between the non-crosslinked part 1 and the crosslinked part 2, but also supplement the nutrients for cell growth for the biological patch.
[0087] The present invention also provides Figure 2 The preparation method of the biological patch of the structure shown in the figure can be prepared by referring to any one of the following two preparation methods, as follows:
[0088] The first preparation method comprises the following steps:
[0089] Mixing a polysaccharide polymer compound aqueous solution and a cross-linking agent to obtain a mixed solution;
[0090] The mixed solution is placed on any surface of the matrix material, and the mixed solution is gradually penetrated into the matrix material to a preset depth to perform a gradient cross-linking reaction to form a cross-linked part 2 and a non-cross-linked part 1. After washing and freeze-drying, a biological patch is obtained, wherein the thickness ratio of the non-cross-linked part 1 to the cross-linked part 2 is 1:99-99:1, the porosity of the non-cross-linked part is greater than the porosity of the cross-linked part, and the porosity difference is greater than or equal to 5%.
[0091] The second preparation method comprises the following steps:
[0092] Mixing a polysaccharide polymer compound aqueous solution and a cross-linking agent to obtain a mixed solution;
[0093] Placing the mixed solution on any surface of the base material, allowing the mixed solution to gradually penetrate into the base material to a preset depth to perform a gradient cross-linking reaction to form a cross-linked portion 2 and a non-cross-linked portion A, and obtaining a prefabricated biological patch after washing;
[0094] An adhesive is placed on the surface of the non-crosslinked part A of the prefabricated biological patch, and then a new matrix material is bonded to the prefabricated biological patch so that the non-crosslinked part A and the new matrix material together constitute a non-crosslinked part 1. After water bathing and freeze drying, a biological patch is obtained, wherein the thickness ratio of the non-crosslinked part 1 to the crosslinked part 2 is 1:10-10:1, the porosity of the non-crosslinked part is greater than the porosity of the crosslinked part, and the porosity difference is greater than or equal to 5%.
[0095] Optionally, the matrix material is selected from dermal acellular matrix or collagen.
[0096] It is understandable that in the present invention, the above two preparation methods can be selected according to actual needs to prepare Figure 2 Biological patch with the structure shown.
[0097] Furthermore, the present invention also provides Figure 3 The method for preparing the biological patch of the structure shown comprises the following steps:
[0098] The polysaccharide polymer compound aqueous solution and the cross-linking agent are mixed, and then an alkaline solution is added to adjust the alkalinity to obtain a mixed solution;
[0099] The mixed solution is placed on any surface of the first matrix material and the second matrix material respectively, and the mixed solution is gradually infiltrated into the first matrix material and the second matrix material to a preset depth to perform a gradient cross-linking reaction to form a first gradient cross-linked part, a first non-cross-linked part 3, a second gradient cross-linked part and a second non-cross-linked part 4, and then washed and freeze-dried to obtain a first intermediate and a second intermediate;
[0100] The binder is placed on the surface of the first gradient cross-linked portion of the first intermediate and / or the second gradient cross-linked portion of the second intermediate, and then the first intermediate and the second intermediate are bonded together, so that the first gradient cross-linked portion and the second gradient cross-linked portion together constitute the cross-linked portion 2, the first non-cross-linked portion 3 and the second non-cross-linked portion 4 together constitute the non-cross-linked portion 1, and the cross-linked portion 2 is located between the first non-cross-linked portion 3 and the second non-cross-linked portion 4, and then subjected to water bath and freeze drying to obtain the following Figure 3 The biological patch shown, wherein the thickness ratio of the non-cross-linked part 1 to the cross-linked part 2 is 1:99-99:1, the porosity of the non-cross-linked part is greater than the porosity of the cross-linked part, and the porosity difference is greater than or equal to 5%.
[0101] It should be noted that the first matrix material and the second matrix material used in the above method can be obtained by cutting a piece of matrix material into two, or can be two complete matrix materials respectively, wherein the first matrix material and the second matrix material are independently selected from dermal acellular matrix or collagen.
[0102] It is understandable that in the present invention, whether Figure 2 The structure shown is Figure 3 The preparation method of the biological patch of the structure shown is to utilize the gravity and fluidity of the mixed solution to gradually penetrate from one side of the base material to the inside, so that the cross-linking agent in the mixed solution can achieve a gradient distribution in the thickness direction of the base material under the action of the polysaccharide polymer compound, thereby achieving the gradual weakening of the reaction degree between collagen and the cross-linking agent along the thickness direction of the base material, presenting different cross-linking degrees, and obtaining a biological patch with a gradient porosity distribution.
[0103] It should be noted that, in the present invention, gradient cross-linking reduces the porosity of the matrix material, mainly because the cross-linking agent acts as a bridge between collagen molecules, prompting the collagen molecules that were previously far apart to form a denser grid structure under the overlap of the cross-linking agent, thereby reducing the porosity of the biological patch; while the polysaccharide polymer compound contributes very little to the dense collagen grid, and its main function is to increase the viscosity of the cross-linking agent solution so that the cross-linking agent can slowly penetrate from one surface of the matrix material into the interior of the matrix material, causing the cross-linking amount along the thickness direction of the matrix material to present a gradient distribution from more to less or from less to more.
[0104] Optionally, the mass fraction of the polysaccharide polymer compound in the polysaccharide polymer compound aqueous solution is 3%-10%. Such a setting is conducive to better achieving gradient cross-linking.
[0105] Furthermore, the polysaccharide polymer compound aqueous solution is selected from at least one of a chitosan aqueous solution, a chitosan derivative aqueous solution, a cellulose aqueous solution, a cellulose derivative aqueous solution, a guar gum aqueous solution, a tamarind gum aqueous solution, a sodium carboxymethyl cellulose aqueous solution, and a sodium carboxymethyl starch aqueous solution.
[0106] Optionally, the viscosity of the mixed solution is 0.01 Pa·s-40000 Pa·s. Such a setting is conducive to regulating the penetration cross-linking time and the cross-linking degree, and controlling the gradient distribution of the porosity of the cross-linked part 2.
[0107] Optionally, the pH value of the mixed solution is 8-14. Such a setting is conducive to promoting the cross-linking reaction.
[0108] Optionally, the mass fraction of the cross-linking agent in the mixed solution is 0.1%-5%; the mass fraction of the polysaccharide polymer compound in the mixed solution is 0.1%-5%. With this arrangement, the gradient cross-linking reaction between the cross-linking agent and the collagen active substance in the matrix material can be controlled by controlling the amounts of the cross-linking agent and the polysaccharide polymer compound, thereby forming a cross-linked part 2 with different cross-linking properties.
[0109] Furthermore, the cross-linking agent is selected from at least one of an aldehyde cross-linking agent, a carboimide, and a glycidyl ether.
[0110] It should be noted that different types of cross-linking agents require different environments for cross-linking with collagen active substances in the matrix material. In the present invention, the acidity and alkalinity of the mixed solution can be adjusted according to the type of cross-linking agent. For example, when the cross-linking agent is selected from aldehyde cross-linking agents or glycidyl ethers, an alkaline solution can be added to the mixed solution to adjust the pH value to 12-13; when the cross-linking agent is selected from carbonimide, the mixed solution can be controlled to be weakly acidic.
[0111] Optionally, the cleaning treatment step includes: first washing with water, then replacing with alcohol, then soaking in an aqueous solution of an anionic descaling agent with a mass fraction of 0.2%-1% to swell for 1h-2h, and finally placing in water, wherein the aqueous solution of the anionic descaling agent is selected from a sodium dodecyl sulfate solution. In this way, the cross-linking agent and polysaccharide polymer compounds that have not reacted completely on the substrate material can be washed away.
[0112] Optionally, the gradient cross-linking reaction temperature is 25° C.-50° C., and the gradient cross-linking reaction time is 0.5 h-48 h. In this way, the thickness of the cross-linked part 2 and the non-cross-linked part 1 can be adjusted.
[0113] It should be noted that the base materials used in the present invention are all freeze-dried base materials, and the preparation of the base materials belongs to conventional technical means, so it will not be described here in detail.
[0114] In addition, the present invention also provides a use of the biological patch as described above in repairing tissue damage.
[0115] Specifically, in one embodiment, the biological patch is used in tendon soft tissue repair.
[0116] The biological patch and its preparation method and application will be further described below through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0117] Meanwhile, it should be noted that the average porosity of the non-crosslinked part, the average porosity of the crosslinked part, and the average porosity of the biological patch involved in the embodiments and comparative examples of the present invention are all tested using an electron scanning microscope (German ZEISS Sigma 300).
[0118] Example 1
[0119] A 5% by mass aqueous solution of hydroxyethyl cellulose and glutaraldehyde are mixed to obtain a first mixed solution, in which the mass fraction of hydroxyethyl cellulose is 2% and the mass fraction of glutaraldehyde is 2%. Then, 5M sodium hydroxide is added to adjust the pH value of the mixed solution to 12 and stir evenly to obtain a second mixed solution.
[0120] The second mixed solution is applied to the surface of a dry dermal acellular matrix, and then a cross-linking reaction is carried out at 40° C. for 6 hours to form a cross-linked part and a non-cross-linked part A, thereby obtaining a cross-linked dermal acellular matrix.
[0121] The cross-linked dermal acellular matrix was washed with water, replaced with ethanol twice, immersed in a 0.5% sodium dodecyl sulfate solution to swell for 1.5 hours, and then replaced with purified water to obtain a prefabricated biological patch.
[0122] A collagen solution is placed on the surface of the non-cross-linked part A of the prefabricated biological patch, and then a new dry dermal decellularized matrix is bonded to the prefabricated biological patch so that the non-cross-linked part A and the new dry dermal decellularized matrix together constitute a non-cross-linked part, and then freeze-dried after being placed in a water bath at 40°C for 5 hours to obtain a biological patch, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 11:9, the average porosity of the non-cross-linked part is 81.15%, the average porosity of the cross-linked part is 0.5%-15%, the thickness of the biological patch is 3 mm, the average pore size is 55.71 μm, and the average porosity is 49.13%.
[0123] The longitudinal cross section of the biological patch prepared in this example was examined using a scanning electron microscope. The examination results are as follows: Figure 5 As shown, from Figure 5 It can be seen that the porosity of the non-crosslinked part is greater than the porosity of the crosslinked part, and the porosity difference is greater than 40%.
[0124] Example 2
[0125] An 8% by mass aqueous solution of hydroxyethyl cellulose and 1,4-butanediol diglycidyl ether are mixed to obtain a first mixed solution, in which the mass fraction of hydroxyethyl cellulose is 4%, and the mass fraction of 1,4-butanediol diglycidyl ether is 4%, and then 5M sodium hydroxide is added to adjust the pH value of the solution to 10 and stir evenly to obtain a second mixed solution.
[0126] The second mixed solution is applied to the surface of the dry dermal acellular matrix, and then a cross-linking reaction is carried out at 35° C. for 8 hours to form a cross-linked part and a non-cross-linked part, thereby obtaining a cross-linked dermal acellular matrix.
[0127] The cross-linked dermal decellularized matrix was washed with water, replaced and exchanged with ethanol twice, immersed in a 0.8% by mass sodium dodecyl sulfate solution for swelling for 1.5 hours, replaced with purified water, and then freeze-dried to obtain a biological patch, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 1:19, the average porosity of the non-cross-linked part is 72.42%, the average porosity of the cross-linked part is 0.1%-10%, the thickness of the biological patch is 1.15 mm, the average pore size is 48.11 μm, and the average porosity is 45.27%.
[0128] Example 3
[0129] The only difference between Example 3 and Example 1 is that a piece of dry dermal acellular matrix is cut transversely into two parts to obtain a first dermal acellular matrix and a second dermal acellular matrix, respectively.
[0130] The second mixed solution is placed on any surface of the first dermal decellularized matrix and the second dermal decellularized matrix respectively, and then a cross-linking reaction is carried out at 40°C for 4 hours to form a first gradient cross-linked part, a first non-cross-linked part, a second gradient cross-linked part and a second non-cross-linked part, and then washed with water, and replaced with ethanol twice, and then immersed in a 0.5% mass fraction sodium dodecyl sulfate solution for swelling for 1.5 hours, and then replaced with purified water to obtain a first intermediate and a second intermediate.
[0131] A collagen solution is placed on the surface of the first gradient cross-linked part of the first intermediate and the second gradient cross-linked part of the second intermediate, and then the first intermediate and the second intermediate are bonded together so that the first gradient cross-linked part and the second gradient cross-linked part together constitute a cross-linked part, and the first non-cross-linked part and the second non-cross-linked part together constitute a non-cross-linked part, followed by freeze-drying after being placed in a water bath at 30°C for 6 hours to obtain a biological patch, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 2:1, the thickness ratio of the first non-cross-linked part to the second non-cross-linked part is 1:1, the average porosity of the non-cross-linked part is 74.41%, the average porosity of the cross-linked part is 2%-20%, the thickness of the biological patch is 3.00 mm, the average pore size is 85.03 μm, and the average porosity is 64.85%.
[0132] Example 4
[0133] The dry dermal acellular matrix was immersed in a 1% by mass aqueous solution of 1,4-butanediol diglycidyl ether, and then subjected to a cross-linking reaction at 30° C. for 12 hours to form a cross-linked part, thereby obtaining a cross-linked dermal acellular matrix.
[0134] The cross-linked dermal acellular matrix was washed with water, replaced with ethanol twice, immersed in a 0.5% sodium dodecyl sulfate solution for swelling for 1.5 hours, and then replaced with purified water to obtain a prefabricated biological patch.
[0135] A collagen solution is placed on the surface of a new dry dermal decellularized matrix, and then the prefabricated biological patch and the new dry dermal decellularized matrix are bonded together to form a non-cross-linked part and a cross-linked part, and then freeze-dried after being placed in a water bath at 37°C for 5 hours to obtain a biological patch, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 1:1, the average porosity of the non-cross-linked part is 76.14%, the average porosity of the cross-linked part is 16.84%, the thickness of the biological patch is 3.00 mm, the average pore size is 64.2 μm, and the average porosity is 58.88%.
[0136] Example 5
[0137] A 5% by mass hydroxyethyl cellulose aqueous solution and 1,4-butanediol diglycidyl ether are mixed to obtain a first mixed solution, in which the mass fraction of hydroxyethyl cellulose is 3%, and the mass fraction of 1,4-butanediol diglycidyl ether is 3%, and then 5M sodium hydroxide is added to adjust the pH value of the solution to 10 and stir evenly to obtain a second mixed solution.
[0138] The second mixed solution is applied to the surface of the dry collagen patch, and then a cross-linking reaction is carried out at 30° C. for 12 hours to form a cross-linked portion and a non-cross-linked distribution, thereby obtaining a cross-linked collagen patch.
[0139] The cross-linked collagen patch was washed with water, replaced with ethanol twice, immersed in a 0.8% by mass sodium dodecyl sulfate solution for swelling for 1.5 hours, replaced with purified water, and then freeze-dried to obtain the biological patch, wherein the thickness ratio of the non-cross-linked part and the cross-linked distribution is 3:10, the average porosity of the non-cross-linked part is 74.31%, the average porosity of the cross-linked part is 35%-55%, the thickness of the biological patch is 1.15 mm, the average pore size is 120.24 μm, and the average porosity is 67.55%.
[0140] Comparative Example 1
[0141] Compared with Example 1, Comparative Example 1 differs only in that the second mixed solution is applied to the surface of a dry dermal acellular matrix, and then a cross-linking reaction is carried out at 40°C for 72 hours to form a cross-linked part and a non-cross-linked part A to obtain a cross-linked dermal acellular matrix. The other conditions are the same to obtain a biological patch, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 0.1:99.9, the average porosity of the non-cross-linked part is 51.41%, the average porosity of the cross-linked part is 0.1%-10%, the thickness of the biological patch is 3.00 mm, the average pore size is 15.23 μm, and the average porosity is 8.95%.
[0142] Comparative Example 2
[0143] Comparative Example 2 is different from Example 1 only in that a 12% mass fraction hydroxyethyl cellulose aqueous solution and 1,4-butanediol diglycidyl ether are mixed to obtain a first mixed solution, in which the mass fraction of hydroxyethyl cellulose is 11% and the mass fraction of 1,4-butanediol diglycidyl ether is 1%, and then 5M sodium hydroxide is added to adjust the pH value of the solution to 12 and stir evenly to obtain a second mixed solution; the second mixed solution is applied to the surface of a dry dermal acellular matrix, and then a cross-linking reaction is carried out at 30°C for 0.5h to form a cross-linked part and a non-cross-linked part A to obtain a cross-linked dermal acellular matrix, and the other conditions are the same to obtain a biological patch, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 99.5:0.5, the average porosity of the non-cross-linked part is 87.48%, the average porosity of the cross-linked part is 5%-15%, the thickness of the biological patch is 3.00mm, the average pore size is 87.15μm, and the average porosity is 85.94%.
[0144] Comparative Example 3
[0145] A 2% by mass hydroxyethyl cellulose aqueous solution and 1,4-butanediol diglycidyl ether are mixed to obtain a first mixed solution, in which the mass fraction of hydroxyethyl cellulose is 1.5% and the mass fraction of 1,4-butanediol diglycidyl ether is 0.1%, and then 5M sodium hydroxide is added to adjust the pH value of the solution to 8 and stir evenly to obtain a second mixed solution; the second mixed solution is applied to a surface of a dry dermal acellular matrix, and then a cross-linking reaction is carried out at 30° C. for 5 hours to form a cross-linked part and a non-cross-linked part, to obtain a cross-linked dermal acellular matrix, The cross-linked dermal decellularized matrix was washed with water, replaced and exchanged with ethanol twice, immersed in a 0.8% by mass sodium dodecyl sulfate solution for swelling for 1.5 hours, replaced with purified water, and then freeze-dried to obtain a biological patch, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 1:4, the average porosity of the non-cross-linked part is 85.4%, the average porosity of the cross-linked part is 81.78%-84.02%, the thickness of the biological patch is 1.15 mm, the average pore size is 98.11 μm, and the average porosity is 84.74%.
[0146] Comparative Example 4
[0147] Comparative Example 4 is different from Example 4 only in that a 0.001% mass fraction of 1,4-butanediol diglycidyl ether solution is applied to the surface of the dry dermal decellularized matrix, and then a cross-linking reaction is carried out at 4°C for 1 hour to form a cross-linked part to obtain a cross-linked dermal decellularized matrix. The other conditions are the same to obtain a biological patch, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 1:1, the average porosity of the non-cross-linked part is 81.30%, the average porosity of the cross-linked part is 79.03%, the thickness of the biological patch is 3.00 mm, the average pore size is 86.94 μm, and the average porosity is 78.89%.
[0148] The biopatch prepared in Examples 1-5 and Comparative Examples 1-4 was tested for degradation performance and mechanical properties at different degradation time periods. The test results are shown in Table 1, wherein the specific test method is as follows:
[0149] Degradation performance test:
[0150] The biological patch prepared according to the above examples or comparative examples was added into 1% pancreatic enzyme solution and soaked at 37° C. for 24 h and 48 h, then taken out, washed and freeze-dried.
[0151] (1) Suture strength test method
[0152] Testing instrument: universal mechanical tensile testing machine.
[0153] The sample was cut into 1cm×1cm test samples, and No. 2 polyethylene surgical suture was used to pass through the edge 3 mm away from the center of the test sample; before the test, the test sample was soaked in saline for 3 minutes; the upper pneumatic grip of the universal mechanical tensile testing machine was used to clamp the test sample about 5 mm from the unpierced suture needle end, and sutured into a semi-circle; the tail of the suture was clamped on the lower grip, stretched at 20mm / min, and the tension-displacement curve was recorded; the maximum value of the measured ce (N) was recorded as the suture strength.
[0154] (2) Maximum tensile force test method
[0155] Testing instrument: universal mechanical tensile testing machine.
[0156] The sample was cut into test samples of 5 mm in length and 50 mm in width, and soaked in physiological saline for 5 min. The test sample was clamped at both ends of the universal mechanical testing machine and the initial distance between the clamps was 3 cm. The test sample was stretched at a stretching speed of 30 mm / min until it broke, and the maximum tensile force ce (N) measured during the test was recorded, i.e. the maximum tensile force.
[0157] (3) Tear strength test method
[0158] Testing instrument: universal mechanical tensile testing machine.
[0159] Prepare a single-sided tearing sample with a long side of 70mm and a short side of 40mm. Pre-tear 50mm at the center of the short side before testing the tear strength. The distance between the clamps of the tensile testing machine is 50mm. Soak the test sample in saline for 3min. Clamp one side of the notch of the test sample with the lower clamp, about 20mm. Fold the other side of the notch of the test sample 180° and load it into the upper clamp, making sure that the long side of the sample is parallel to the tensile testing machine. The minimum width of the clamp is 50±2mm. Stretch at a rate of 100±20mm / min until the sample breaks. Record the force-distance diagram and calculate the tear strength: calculate the peak-to-valley average of the force peak, i.e., the tear strength (N).
[0160] Table 1
[0161]
[0162] It should be noted that the matrix material used in Example 5 is collagen. Compared with the mechanical properties of the dermal decellularized matrix itself, the mechanical properties of collagen itself are lower. Therefore, the suture strength, maximum tensile force and tear strength of the biological patch obtained in Example 5 are necessarily lower than the suture strength, maximum tensile force and tear strength of the biological patch obtained in the embodiment using the dermal decellularized matrix as the matrix material.
[0163] In addition, the present invention applies the biological patch prepared by Examples 1-5 and Comparative Examples 1-4 to the repair of New Zealand white rabbit rotator cuff tissue, and the specific experimental method is as follows: the white rabbit is anesthetized by ear vein, and the skin of the shoulder joint of the left forelimb is prepared after the anesthesia is successful. An incision of about 4 cm is made along the longitudinal axis of the shoulder joint, and the skin and subcutaneous tissue are cut layer by layer to expose the rabbit supraspinatus tendon. The supraspinatus muscle is removed from the greater tubercle of the humeral head to the belly of the muscle with a blade, with a range of 1.5 cm × 1.5 cm, and the incision is sutured after direct washing with saline. After the rotator cuff defect is created in the experimental group, two medullary tracts with a diameter of 2 mm are drilled at the greater tubercle with an electric drill, and the spacing between the two medullary tracts is 1.5 cm. The cross-linked patch prepared by Examples 1-5 and Comparative Examples 1-4 is sterilized and cut into a sheet sample of 1.5 cm × 1.5 cm, and one end of the patch is fixed at the greater tubercle through a tunnel using a 2-0 tendon line, and the other end is sutured with the stump of the supraspinatus muscle. The incision is sutured layer by layer after washing with saline. The other right forelimb was not treated and was regarded as a control.
[0164] The experimental results show that the biological patches prepared using the embodiments of the present invention survived within 24 weeks after the repair surgery, the incisions healed well and no rejection symptoms such as infection or inflammation occurred; and within 12 to 24 weeks after the repair surgery, the left shoulder movements of all experimental rabbits were basically normal, and there was no fracture in the repaired rotator cuff tissue; while the experimental rabbits repaired with the biological patches prepared using comparative examples 1-4 survived within 24 weeks after the repair surgery, but the incisions healed poorly, and aseptic infections such as chronic inflammation or re-tears occurred.
[0165] Therefore, in the present invention, there is a synergistic relationship between the thickness of the non-cross-linked part and the cross-linked part, as well as the porosity of the non-cross-linked part and the porosity difference of the cross-linked part. Under the synergistic effect of the two, the overall degradation rate of the biological patch can be effectively controlled within an appropriate range, and the relationship between the collagen bioactivity and degradation time in the biological patch can be balanced, so that the biological patch can prolong its degradation time in the body, maintain good mechanical properties, and maintain high collagen bioactivity.
[0166] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0167] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A biological patch, characterized in that: The biological patch includes a matrix, and along the thickness direction of the biological patch, the matrix includes a non-cross-linked part and a cross-linked part, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 1:99-99:1, the porosity of the non-cross-linked part is greater than the porosity of the cross-linked part, and the porosity difference is greater than or equal to 5%.
2. The biological patch according to claim 1, characterized in that: The average porosity of the non-crosslinked part is 40%-90%; And / or, the average porosity of the cross-linked portion is 0.1%-40%.
3. The biological patch according to claim 1, characterized in that: In a direction from the cross-linked portion to the non-cross-linked portion, the porosity of the cross-linked portion is the same, or the porosity of the cross-linked portion increases gradually.
4. The biological patch according to claim 3, characterized in that: When the porosity of the cross-linked portion is the same, the thickness ratio of the non-cross-linked portion to the cross-linked portion is 1:9-9:
1.
5. The biological patch according to claim 3, characterized in that: When the porosity of the cross-linked portion increases gradually, the thickness ratio of the non-cross-linked portion to the cross-linked portion is 1:99-99:
1.
6. The biological patch according to claim 3, characterized in that: When the porosity increases gradually, the cross-linked part contains polysaccharide polymers, and the average cross-linking degree of the polysaccharide polymers is 0.1%-50%.
7. The biological patch according to claim 6, characterized in that: The polysaccharide polymer is selected from at least one of chitosan, chitosan derivatives, cellulose, cellulose derivatives, guar gum, tamarind gum, sodium carboxymethyl cellulose, and sodium carboxymethyl starch.
8. The biological patch according to claim 1, characterized in that: The non-cross-linked portion includes a first non-cross-linked portion and a second non-cross-linked portion, and the cross-linked portion is arranged between the first non-cross-linked portion and the second non-cross-linked portion. From the first non-cross-linked portion to the second non-cross-linked portion, the pores of the cross-linked portion first decrease and then increase.
9. The biological patch according to claim 8, characterized in that: A thickness ratio of the first non-crosslinked portion to the second non-crosslinked portion is 1:9-9:
1.
10. The biological patch according to any one of claims 1 to 9, characterized in that: A bonding layer is also provided between the non-crosslinked part and the crosslinked part, and the thickness of the bonding layer is 0.1%-20% of the total thickness of the substrate; And / or, the material of the matrix is selected from dermal acellular matrix or collagen.
11. The biological patch according to claim 10, characterized in that: The thickness of the biological patch is 0.5mm-5.5mm; And / or, the average pore size of the biological patch is 0.1 μm-500 μm, and the average porosity is 10%-80%.
12. A method for preparing a biological patch, characterized in that: The steps include: Mixing a polysaccharide polymer compound aqueous solution and a cross-linking agent to obtain a mixed solution; Placing the mixed solution on any surface of a base material, allowing the mixed solution to gradually penetrate into the base material to a preset depth to perform a gradient cross-linking reaction to form a cross-linked part and a non-cross-linked part, and obtaining a biological patch after washing and freeze-drying, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 1:99-99:1, the porosity of the non-cross-linked part is greater than the porosity of the cross-linked part, and the porosity difference is greater than or equal to 5%; Alternatively, a polysaccharide polymer compound aqueous solution and a cross-linking agent are mixed to obtain a mixed solution; Placing the mixed solution on any surface of the base material, allowing the mixed solution to gradually penetrate into the base material to a preset depth to perform a gradient cross-linking reaction to form a cross-linked portion and a non-cross-linked portion A, and obtaining a prefabricated biological patch after washing; An adhesive is placed on the surface of the non-crosslinked part A of the prefabricated biological patch, and then a new matrix material is bonded to the prefabricated biological patch so that the non-crosslinked part A and the new matrix material together constitute a non-crosslinked part. After water bathing and freeze drying, a biological patch is obtained, wherein the thickness ratio of the non-crosslinked part to the crosslinked part is 1:10-10:1, the porosity of the non-crosslinked part is greater than the porosity of the crosslinked part, and the porosity difference is greater than or equal to 5%.
13. The method for preparing the biological patch according to claim 12, characterized in that: The preparation method of the biological patch also satisfies at least one of the following conditions: (1) The mass fraction of the polysaccharide polymer compound in the polysaccharide polymer compound aqueous solution is 3%-10%, wherein the polysaccharide polymer compound aqueous solution is at least one selected from a chitosan aqueous solution, a chitosan derivative aqueous solution, a cellulose aqueous solution, a cellulose derivative aqueous solution, a guar gum aqueous solution, a tamarind gum aqueous solution, a sodium carboxymethyl cellulose aqueous solution, and a sodium carboxymethyl starch aqueous solution; (2) The viscosity of the mixed solution is 0.01 Pa·s-40000 Pa·s, and the pH value is 8-14; (3) The mass fraction of the cross-linking agent in the mixed solution is 0.1%-5%, wherein the cross-linking agent is selected from at least one of an aldehyde cross-linking agent, a carboimide, and a glycidyl ether; (4) The mass fraction of the polysaccharide polymer compound in the mixed solution is 0.1%-5%; (5) The gradient cross-linking reaction temperature is 25°C-50°C, and the gradient cross-linking reaction time is 0.5h-48h; (6) The cleaning treatment step includes: first washing with water, then replacing with alcohol, then soaking in an aqueous solution of an anionic descaling agent with a mass fraction of 0.2% to 1% to swell for 1 h to 2 h, and finally placing in water; (7) The matrix material is selected from dermal acellular matrix or collagen.
14. A method for preparing a biological patch, characterized in that: The steps include: Mixing a polysaccharide polymer compound aqueous solution and a cross-linking agent to obtain a mixed solution; The mixed solution is placed on any surface of the first matrix material and the second matrix material respectively, and the mixed solution is gradually infiltrated into the first matrix material and the second matrix material to a preset depth to perform a gradient cross-linking reaction to form a first gradient cross-linked portion, a first non-cross-linked portion, a second gradient cross-linked portion, and a second non-cross-linked portion, and then washed and freeze-dried to obtain a first intermediate and a second intermediate; A binder is placed on the surface of the first gradient cross-linked part of the first intermediate and / or the second gradient cross-linked part of the second intermediate, and then the first intermediate and the second intermediate are bonded together, so that the first gradient cross-linked part and the second gradient cross-linked part together constitute a cross-linked part, the first non-cross-linked part and the second non-cross-linked part together constitute a non-cross-linked part, and the cross-linked part is located between the first non-cross-linked part and the second non-cross-linked part, and a biological patch is obtained after water bathing and freeze drying, wherein the thickness ratio of the non-cross-linked part to the cross-linked part is 1:10-10:1, the porosity of the non-cross-linked part is greater than the porosity of the cross-linked part, and the porosity difference is greater than or equal to 5%.
15. The method for preparing the biological patch according to claim 14, characterized in that: The preparation method of the biological patch also satisfies at least one of the following conditions: (1) The mass fraction of the polysaccharide polymer compound in the polysaccharide polymer compound aqueous solution is 3%-10%, wherein the polysaccharide polymer compound aqueous solution is at least one selected from a chitosan aqueous solution, a chitosan derivative aqueous solution, a cellulose aqueous solution, a cellulose derivative aqueous solution, a guar gum aqueous solution, a tamarind gum aqueous solution, a sodium carboxymethyl cellulose aqueous solution, and a sodium carboxymethyl starch aqueous solution; (2) The viscosity of the mixed solution is 0.01 Pa·s-40000 Pa·s, and the pH value is 8-14; (3) The mass fraction of the cross-linking agent in the mixed solution is 0.1%-5%, wherein the cross-linking agent is selected from at least one of an aldehyde cross-linking agent, a carboimide, and a glycidyl ether; (4) The mass fraction of the polysaccharide polymer compound in the mixed solution is 0.1%-5%; (5) The gradient cross-linking reaction temperature is 25°C-50°C, and the gradient cross-linking reaction time is 0.5h-48h; (6) The cleaning treatment step includes: first washing with water, then replacing with alcohol, then soaking in an aqueous solution of an anionic descaling agent with a mass fraction of 0.2% to 1% to swell for 1 h to 2 h, and finally placing in water; (7) The first matrix material and the second matrix material are independently selected from dermal acellular matrix or collagen.
16. Use of the biological patch according to any one of claims 1 to 11 in repairing tissue damage.
Citation Information
Cited By
Biological patch, preparation method therefor, and use thereof
WO2026119199A1